Chris McGonigle at the waterfront of Kilkeel fishing harbour in Northern Ireland. - Alan McCulla:::Creator:::::::::::: (Northern Ireland; United Kingdom, 2023)
Author Chris McGonigle at the working waterfront of Kilkeel the largest fishing harbour. Kilkeel is a small town in County Down, Northern Ireland. This photograph and this article "None of it is important or all of it is" Steinbeck, Ricketts, Ecology, and Identity, appears in Steinbeck Review, vol.16, no.2, 2022.